Recent trends in emerging greywater management in India: An overview - Rakshit Jakhar; Katarzyna Styszko (Desalination and Water Treatment)
Water, one of the most essential resources, is intrinsic to sustaining life. However, less than 5 % of fresh water is available in usable form. Over the past few decades, significant changes in water consumption patterns have severely impacted the availability of fresh water. Major factors such as global warming, rapid urbanisation, and excessive water use have resulted in global water scarcity. Due to our continued exploitation of freshwater resources, there is an urgent need to explore sustainable methods to reduce reliance on freshwater for various activities. Greywater technology implementation is one promising solution. In a typical residence, greywater, which includes all household wastewater excluding toilet waste, accounts for 60–80 % of daily wastewater and is characterised by its low organic concentration and high volume. This issue could pose a challenge to large urban wastewater treatment plants designed for high-strength operations. Therefore, it is vital to separate greywater at the source for decentralised wastewater treatment, ensuring proper management through distinct treatment procedures. Greywater reuse can enhance the resilience and adaptability of local water systems, reduce transportation costs, and achieve reuse standards suitable for its intended applications. This study aims to provide a comprehensive overview of current and emerging greywater treatment methods. Nature-based solutions, biofilm technologies, and membrane bioreactors (MBRs) are biological treatment technologies that can be used together with physicochemical treatment technologies like membrane filtration, sorption, ion exchange, and ultraviolet (UV) disinfection to make treated water that meets standards for reuse. This study addresses innovative solutions to challenges such as demographic variation in greywater quality, the lack of a legislative framework for greywater management, monitoring and control systems, and consumer perceptions of greywater reuse with potassium rich biochar. The study concludes by highlighting the advantages of greywater reuse in urban settings, which include potential water and energy savings and the promotion of a sustainable future. Public awareness and social engagement are critical for the successful implementation of greywater reuse practices.